METASTRONGYLOSIS IN A NON-DESCRIPTIVE PIG IN TAMIL NADU - C. Soundararajan; A. Raman; A. Komathi; C.J. Johannah Nitisha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Lungworms are found to be a serious problem in pigs by causing severe infections.  The  worms  were  collected  during  post  mortem  from  a  6  year  old male, non – descriptive pig at Periyeri hamlet of Thurinjikuppam, Polur taluk, Thiruvannamalai district, Tamil Nadu which was raised and hand fed as a single animal and had access to the agricultural field. On post mortem examination, the trachea was severely congested and occluded with pus and the lungs were congested in which the lung worms wriggled out with pus while sectioning the lungs. The worms were morphologically identified as Metastrongylus sp.in a non-descriptive pig in Tamil Nadu.